2016
DOI: 10.1530/rep-15-0523
|View full text |Cite
|
Sign up to set email alerts
|

Maternal diabetes promotes mTORC1 downstream signalling in rabbit preimplantation embryos

Abstract: The mammalian target of rapamycin complex 1 (mTORC1) is known to be a central cellular nutrient sensor and master regulator of protein metabolism; therefore, it is indispensable for normal embryonic development. We showed previously in a diabetic pregnancy that embryonic mTORC1 phosphorylation is increased in case of maternal hyperglycaemia and hypoinsulinaemia. Further, the preimplantation embryo is exposed to increased L-leucine levels during a diabetic pregnancy. To understand how mTOR signalling is regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 51 publications
1
21
0
Order By: Relevance
“…Embryos are acutely sensitive to nutrient imbalances or deprivation. Signalling through adenosine monophosphate-activated kinase (AMPK) and mammalian target of rapamycin (mTOR) mediates responses to nutritive stress in embryos [ 12 , 13 ], leading to increased endocytosis and autophagy [ 14 , 15 ], altered trophoblast differentiation [ 16 ], and ultimately offspring health consequences [ 17 , 18 ]. However, unlike these pathways which transduce signals through protein phosphorylation, post-translational modification with O-linked β-N-acetylglucosamine (O-GlcNAcylation) is recognised as an important cellular response to a wide range of environmental stressors, including osmotic, oxidative, temperature and genotoxic stresses [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Embryos are acutely sensitive to nutrient imbalances or deprivation. Signalling through adenosine monophosphate-activated kinase (AMPK) and mammalian target of rapamycin (mTOR) mediates responses to nutritive stress in embryos [ 12 , 13 ], leading to increased endocytosis and autophagy [ 14 , 15 ], altered trophoblast differentiation [ 16 ], and ultimately offspring health consequences [ 17 , 18 ]. However, unlike these pathways which transduce signals through protein phosphorylation, post-translational modification with O-linked β-N-acetylglucosamine (O-GlcNAcylation) is recognised as an important cellular response to a wide range of environmental stressors, including osmotic, oxidative, temperature and genotoxic stresses [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the top 10 deregulated miRNAs, the study selected 7 miRNAs, which its biological targets were related to proliferation, differentiation, and cellular apoptosis processes. As could be The mammalian target of rapamycin complex 1 (mTORC1) is known to be indispensable for healthy embryonic development, has how to function to regulate the balance between growth and autophagy in physiological conditions and environmental stress (Gürke et al, 2016). It has been suggested that mTOR signaling plays a central role in the perception and response to intracellular nutrient availability (Xiang et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The mRNA from single blastocysts, embryoblasts and trophoblasts was extracted with Dynabeads ® Oligo (dT)25 (Invitrogen) and used for cDNA synthesis as described previously (Gürke et al., ). cDNAs were adjusted to total volumes of 100 μl and 80 μl for single blastocyst and embryoblasts or trophoblasts, respectively.…”
Section: Methodsmentioning
confidence: 99%